As profanações de Hilda Hilst em Tu não te moves de ti - Vieira, Blenda Ramos (2012)
This paper studies the terms sacred and profane in the book Tu não te moves de ti written by Hilda Hilst. Many authors point relevant factors to the study of these terms, as Emile Durkhein, which in one of his studies says that between the sacred and profane there is a dualistic view, which means, the opposition, but that cannot be separated. In this point, sacred are considered the manifestations of a different natural reality, referring to the extraordinary, the unusual, the transcendental, and the metaphysical. When the process is treated as a natural, biological, normal, it is profane, everything that is not sacred. According to Agamben, profane was all that once was sacred or religious, and t is returned to the use of man, failing to remain untouched. Regarding the two conceptions of the terms mentioned above, it is possible to have a discussion with attention paid to changes in concepts of sexuality and eroticism in the literature. The work passes by the relevance of sacred and profane body, and observes these changes in Hilst s work, always seeking the game that the author makes between these terms. The text chosen, Tu não te moves de ti, is a work composed of three novellas: \"Tadeu (da razão)\", \"Matamoros (da fantasia)\" and \"Axelrod (da proporção),\" which at first seem disconnected, but are totally intertwined. Tu não te moves de ti plays a role in revealing flaws and wonders and obscurities of man. Therefore, we develop a study on the establishment of the work and how we can define manifestations of the sacred and profane from the main characters of each novella, based on authors such as Emile Durkhein, Mircea Eliade and Giorgio Agamben.